NOISE AWARE BAYESIAN PARAMETER ESTIMATION IN BIOPROCESSES: USING NEURAL NETWORK SURROGATE MODELS WITH NON-UNIFORM DATA SAMPLING - Weir, Lauren (My University, 2024)
This thesis demonstrates a parameter estimation technique for bioprocesses that utilizes measurement noise in experimental data to determine credible intervals on parameter estimates, with this information of potential use in prediction, robust control, and optimization. To determine these estimates, the work implements Bayesian inference using nested sampling, presenting an approach to develop neural network (NN) based surrogate models. To address challenges associated with non-uniform sampling of experimental measurements, an NN structure is proposed. The resultant surrogate model is utilized within a Nested Sampling Algorithm that samples possible parameter values from the parameter space and uses the NN to calculate model output for use in the likelihood function based on the joint probability distribution of the noise of output variables. This method is illustrated against simulated data, then with experimental data from a Sartorius fed-batch bioprocess. Results demonstrate the feasibility of the proposed technique to enable rapid parameter estimation for bioprocesses.
NOISE AWARE BAYESIAN PARAMETER ESTIMATION IN BIOPROCESSES
Keywords: Bayesian Inference; Surrogate Modelling; Bioprocess; Parameter Estimation; Non-uniform sampling